Professional Attitude of Physical Education Teachers toward Education Process of Students with Severe Intellectual Disabilities - Klaviņa, Aija; Strazdiņa, Nadija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Physical education teachers face many challenges when teaching students with severe intellectual disability (SID) because of extensive adaptations and assistance they need. The purpose of this study was to determine attitude of PE teachers in Latvia and Lithuania toward teaching students with SID in the special education environment. Method: Participants were 84 PE teachers from special schools. The Survey of Physical Education Teachers’ Attitude Toward Teaching Students with SID (Strazdina & Klavina, 2012) was used. Results and Conclusions: Results revealed significant differences in results across teachers’ age, gender and work experience. Latvian teachers' beliefs were more positive towards teaching students with SID than teachers in Lithuania. Stepwise multiple regressions analyses demonstrated that overall there was significant relationship between predictors and behavioral intention.